A Strategi Komunikasi Paslon Prabowo Gibran dalam Meningkatkan Kesadaran dan Partisipasi Gen Z dan Milenial dalam Pemilu 2024 - Ginasari, Wismayanti; Firmansyah, Firmansyah; Pamungkas, Yan Ridwan Putra; Sukandar, Nadya Hapsari Thrisianingsih (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
This research examines changes in Prabowo Subianto's political image and a campaign approach that is more attractive to the younger generation, especially millennials and Gen Z, in the context of the 2024 election in Indonesia. With a focus on the use of social media and innovative communication strategies, this research explores how candidate pair Prabowo and Gibran Rakabuming Raka use 'gemoy' imagery and creative gimmicks to create a unique impression and increase their popularity among young voters. Prabowo and Gibran's communication strategies are explained using PESTEL analysis, AIDA, communication strategy decisions, and the 6C Model. Research findings show that this approach is effective in attracting the attention, increasing popularity, and participation of young voters, who are an important segment in elections. Keyword: marketing communication strategies, campaign advertising, social media